Circus Artists and Romanies:: crossing paths - de Carvalho Lopes, Daniel; Toyansk Guimarais, Marcos; Silva, Erminia (Revista Brasileira de Estudos da Presença, 2025)
The Romanies and circus performers constitute diverse and complex groups that, under specific circumstances, have intermingled and evolved into circus performers of Romani origin. As a result, they share similarities in their lifestyles and artistic production. In this context, this article examines the encounters and influences that shaped their identities as professional, familial, and cultural groups, through the cross-referencing of various sources. It becomes evident that Romani circus performers have begun to adapt their habits, expanding their relationships with non-Romanies, and that the itinerant nature of circus life is both an economically driven choice and a constraint shaped by prejudice.